Reporting misstatements as revisions: An evaluation of managers' use of materiality discretion - Thompson, Rachel A. (Contemporary Accounting Research, 2023)
Abstract In recent years, firms reporting revisions of prior financial statements outnumber those reporting restatements. Misstatements that are material to prior periods are required to be reported as restatements, whereas immaterial errors can be reported as revisions. Based on SEC guidance and widely used materiality benchmarks, I find a significant percentage (29%) of revisions are suspect in that they meet at least one materiality criterion. These suspect revisions are 15% to 29% more likely to be reported when managers have a strong incentive to avoid restatements—when they face the threat of a compensation clawback for reporting a restatement. This result is especially salient when the clawback policy does not require misconduct for recoupment and when the error correction significantly reduces prior period net income. Overall, this evidence suggests that some managers use materiality discretion opportunistically to report misstatements as revisions instead of restatements.